Geographical Variation in Phenotypic Plasticity of Intertidal Sister Limpet’s Species Under Ocean Acidification Scenarios - Lardies, Marco Antonio; Caballero, Paz; Duarte, Cristián; Poupin, María Josefina (Frontiers in Marine Science, 2021)
Ocean Acidification (OA) can have pervasive effects in calcifying marine organisms, and a better understanding of how different populations respond at the physiological and evolutionary level could help to model the impacts of global change in marine ecosystems. Due to its natural geography and oceanographic processes, the Chilean coast provides a natural laboratory where benthic organisms are frequently exposed to diverse projected OA scenarios. The goal of this study was to assess whether a population of mollusks thriving in a more variable environment (Talcaruca) would present higher phenotypic plasticity in physiological and morphological traits in response to different pCO2 when compared to a population of the same species from a more stable environment (Los Molles). To achieve this, two benthic limpets (Scurria zebrina and Scurria viridula) inhabiting these two contrasting localities were exposed to ocean acidification experimental conditions representing the current pCO2 in the Chilean coast (500 μatm) and the levels predicted for the year 2100 in upwelling zones (1500 (μatm). Our results show that the responses to OA are species-specific, even in this related species. Interestingly, S. viridula showed better performance under OA than S. zebrina (i.e., similar sizes and carbonate content in individuals from both populations; lower effects of acidification on the growth rate combined with a reduction of metabolism at higher pCO2). Remarkably, these characteristics could explain this species’ success in overstepping the biogeographical break in the area of Talcaruca, which S. zebrina cannot achieve. Besides, the results show that the habitat factor has a strong influence on some traits. For instance, individuals from Talcaruca presented a higher growth rate plasticity index and lower shell dissolution rates in acidified conditions than those from Los Molles. These results show that limpets from the variable environment tend to display higher plasticity, buffering the physiological effects of OA compared with limpets from the more stable environment. Taken together, these findings highlight the key role of geographic variation in phenotypic plasticity to determine the vulnerability of calcifying organisms to future scenarios of OA.